Community-based natural resource management issues and cases from South Asia - Menon, Ajit 1966-; Singh, Praveen; Shah, Esha; Lele, Sharachchandra; Paranjape, Suhas; Joy, K.J
This work examines the discourse and practice of NGO-driver CBNRM in South Asia and explores to what extent it continues to offer an 'alternative' vision for future developments. The authors do so by examining the outcomes of the interventions studies and the strategies used to achieve them